2007
DOI: 10.1128/cmr.00001-07
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemases: the Versatile β-Lactamases

Abstract: SUMMARY Carbapenemases are β-lactamases with versatile hydrolytic capacities. They have the ability to hydrolyze penicillins, cephalosporins, monobactams, and carbapenems. Bacteria producing these β-lactamases may cause serious infections in which the carbapenemase activity renders many β-lactams ineffective. Carbapenemases are members of the molecular class A, B, and D β-lactamases. Class A and D enzymes have a serine-based hydrolytic mechanism, while class B enzymes are metallo-β-lactamases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
1,877
10
164

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,256 publications
(2,065 citation statements)
references
References 259 publications
(277 reference statements)
14
1,877
10
164
Order By: Relevance
“…1,2 However, the recent emergence of class A b-lactamases capable of hydrolyzing carbapenems threatens this class of b-lactam antibiotics. [3][4][5][6] One of these blactamases, KPC-2, is becoming a major healthcare threat in the United States and throughout the world. 5,7,8 KPC-2 manifests a very broad substrate profile including penicillins, extended-spectrum cephalosporins, cephamycins, and carbapenems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, the recent emergence of class A b-lactamases capable of hydrolyzing carbapenems threatens this class of b-lactam antibiotics. [3][4][5][6] One of these blactamases, KPC-2, is becoming a major healthcare threat in the United States and throughout the world. 5,7,8 KPC-2 manifests a very broad substrate profile including penicillins, extended-spectrum cephalosporins, cephamycins, and carbapenems.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] One of these blactamases, KPC-2, is becoming a major healthcare threat in the United States and throughout the world. 5,7,8 KPC-2 manifests a very broad substrate profile including penicillins, extended-spectrum cephalosporins, cephamycins, and carbapenems. 9,10 Moreover, Papp-Wallace et al showed that this enzyme is resistant to b-lactamase inhibitors (clavulanic acid, sulbactam, and tazobactam), which are typically given in combination with a b-lactam for the treatment of infections caused by b-lactamase producing pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of ESBL production was performed by phenotypic testing based on demonstration of synergy between clavulanic acid and extendedspectrum cephalosporins [2]. Carbapenemase production was detected by the modified Hodge test, and MBL production was further detected by phenotypic methods based on the demonstration of synergy between imipenem and ethylene diamine tetra-acetic acid (EDTA) [specifically, a three-fold or greater decrease in the imipenem minimum inhibitory concentration (MIC) in the presence of EDTA] [3].…”
Section: Mdr Enterobacteriaceae Clinical Isolates Identified Betweenmentioning
confidence: 99%
“…Carbapenems, once considered the mainstay of therapy for systemic infections caused by Enterobacteriaceae isolates with multidrug resistance, may be found to be microbiologically inactive against contemporary isolates owing to the presence of various specific mechanisms of resistance. These include the expression of serine carbapenemases and metallo--lactamases (MBLs) or decreased porin expression in conjunction with extended-spectrum -lactamase (ESBL) or AmpC -lactamase production [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, carbapenemases were originally described as species-specific, chromosomally encoded β-lactamases (Queenan and Bush, 2007), and environmental strains have repeatedly been identified as reservoirs for progenitors of globally disseminating plasmid-encoded carbapenemases. For example, Acinetobacter radioresistens has been identified as the source of a chromosomal blaOXA-23-like gene, which is currently widespread as a plasmid-encoded blaOXA-23 in Acinetobacter baumannii (Poirel et al, 2008).…”
mentioning
confidence: 99%